Determinants of the degree of acceptability of the hospital diet: tools for clinical practice? - Pinto, Elaine De Oliveira; Ribas, Simone Augusta; Rodrigues, Camila Batista (Seven Editora, 2023)
The purpose of the study was to investigate the degree of acceptability of the hospital diet in patients admitted to a public university hospital in the city of Rio de Janeiro. This is a cross-sectional study in which quantitative and environmental aspects related to diet, average length of hospital stay and quality of care were investigated. The results revealed that the evaluation of the acceptance of the hospital diet was considered good to excellent in most cases and that 88.7% of the patients ingested more than half of the total content of the meal offered. In small meals, nutrient-restricted diets, including hyposodic diets, showed a higher degree of acceptance among their users than basic and salt-based diets. The inadequate temperature of the diet served was the factor that most negatively contributed to food acceptance, followed by the lack of interval between dinner and supper. The acceptance of the diet was also inversely proportional to the time of hospitalization. It is concluded that the evaluation of the hospital diet should be carried out continuously and comprehensively, so that the factors that influence user satisfaction can be detected and modified before compromising their nutritional and pathophysiological status.DOI: https://doi.org/10.56238/devopinterscie-013